SPTEdb: a database for transposable elements in salicaceous plants. (9th March 2018) - Yi, Fei; Jia, Zirui; Xiao, Yao; Ma, Wenjun; Wang, Junhui
Abstract: Although transposable elements (TEs) play significant roles in structural, functional and evolutionary dynamics of the salicaceous plants genome and the accurate identification, definition and classification of TEs are still inadequate. In this study, we identified 18 393 TEs from Populus trichocarpa, Populus euphratica and Salix suchowensis using a combination of signature-based, similarity-based and De novo method, and annotated them into 1621 families. A comprehensive and user-friendly web-based database, SPTEdb, was constructed and served for researchers. SPTEdb enables users to browse, retrieve and download the TEs sequences from the database. Meanwhile, several analysis tools, including BLAST, HMMER, GetORF and Cut sequence, were also integrated into SPTEdb to help users to mine the TEs data easily and effectively. In summary, SPTEdb will facilitate the study of TEs biology and functional genomics in salicaceous plants. Database URL : http://genedenovoweb.ticp.net:81/SPTEdb/index.php